2010
DOI: 10.1108/17410401011038892
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of performance metrics in a multi‐enterprise agribusiness

Abstract: Purpose -To examine the disconnect that can develop between corporate goals and those of individual intra-organisational business units arranged as an internal supply chain within a large vertically integrated agribusiness. To explore and discuss the development of a holistic performance metrics system that facilitates internal supply chain coordination and cohesion while allowing synergies to develop across the company.Design/methodology/approach -A case study approach involving a participative action researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…3926/jiem.489 applied performance measurement in the business of manufacturing and services. For instance, (Bryceson & Slaughter, 2010) studied and discussed the holistic performance metric system that improve internal supply chain coordination. Chen & Chen (2007) studied a combination of the data envelopment analysis (DEA) and BSC and another study showed effective quality management through third-generation balanced scorecard (Andersen, Lawrie & Savic, 2004).…”
Section: Trends In Performance Measuresmentioning
confidence: 99%
“…3926/jiem.489 applied performance measurement in the business of manufacturing and services. For instance, (Bryceson & Slaughter, 2010) studied and discussed the holistic performance metric system that improve internal supply chain coordination. Chen & Chen (2007) studied a combination of the data envelopment analysis (DEA) and BSC and another study showed effective quality management through third-generation balanced scorecard (Andersen, Lawrie & Savic, 2004).…”
Section: Trends In Performance Measuresmentioning
confidence: 99%
“…The alternative is to relate individual functional strategies without extracting specific designs related to the supply chain collaborated performance. This would hardly lead to improved performance, because even within one company, there are a number of operational designs, requiring different operational strategies, which are not isolated entities (Kaplan and Norton 1996, Frohlich and Westbrook 2001, Jayaram and Tan 2010, Bryceson and Slaughter 2010, Prajogo and Olhager 2012, Sukati et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional wisdom supported by existing research (Beheshti, 2010;Bryceson and Slaughter, 2010) suggests that decentralised supply chains lead to inefficient flows: materials downstream and information upstream are often non-coordinated, generating forecast excesses. With decentralised supply chain we define those chains whose decision-making power is often decentralised.…”
Section: Introductionmentioning
confidence: 99%